Screening of genotoxicity and mutagenicity in extractable organics from oil sands process–affected water. (9th December 2016) - Zetouni, Nikolas C.; Siraki, Arno G.; Weinfeld, Michael; Pereira, Alberto Dos Santos; Martin, Jonathan W.
Abstract: Large volumes of oil sands process–affected water (OSPW) are produced by the oil sands surface mining industry during alkaline hot‐water extraction of bitumen. It is well documented that the acid extractable organics (AEOs) in OSPW, a highly complex mixture of acidic and polar neutral substances, are acutely toxic; but few studies have examined the genotoxicity or mutagenicity of this mixture. In the present study, the in vitro SOS Chromotest and the Ames test (TA98 and TA100 strains) were used to evaluate genotoxicity and mutagenicity for whole OSPW AEOs in the presence and absence of biotransformation by rat S9 liver enzymes. Two subfractions were also examined in the same assays: neutral extractable fraction (F1‐NE), and the subsequent acid extractable fraction (F2‐AE). In the SOS assay, whole AEO was cytotoxic when concentrated 2× (i.e., twice as concentrated as the environmental sample) and showed increasing genotoxic response above 6×. Co‐exposure with S9 had a protective effect on the cell SOS‐inducing factor and survival but did not eliminate genotoxicity above 6× concentrations. Most of the cytotoxicity was attributable to F2‐AE, but both F1‐NE and F2‐AE had similar genotoxic dose–responses above 6×. In the Ames test without S9, whole AEO was mutagenic in both strains above 10× concentrations. Co‐incubation with S9 had little effect on the TA100 strain but with TA98 resulted in bioactivation at midlevel doses (1.5–6.3×) and protection at higher doses (10–25×). The 2 subfractions were mutagenic in both strains but with different dose–responses. Further research in vivo or in more relevant cells is warranted to investigate the carcinogenic risks of OSPW. Environ Toxicol Chem 2017;36:1397–1404. © 2016 SETAC